Analisis Struktural Puisi “ Aku Ingin” Karya Sapardi Djoko Damono (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Poetry research can be defined as the result of research or the process of analyzing poetry. Poetry is one type of literary genre that expresses the poet's feelings. The series of words are beautiful, contain deep meaning and touch the hearts of the readers. This research aims to know and describe the physical structure and inner structure of poetry contained in the poem Aku Ingin by Sapardi Djoko Damono with a structural approach. The method used in this research is descriptive qualitative method, namely science that aims to describe the deep and intact content in the poem